Comparison of two neoadjuvant chemoradiotherapy regimens in patients with potentially curable esophageal carcinoma. Issue 4 (5th September 2013) - Blom, R. L. G. M.; Sosef, M. N.; Nap, M.; Lammering, G.; van den, F.; Hulshof, M. C. C. M.; Meijer, S. L.; Wilmink, H. W.; van, M. I.
Summary The implementation of neoadjuvant chemoradiotherapy (CRT) in esophageal cancer (EC) patients has led to improved survival rates. Worldwide, different CRT regimens are applied. It is unknown how these regimens relate to each other regarding efficacy. Therefore, the aim of this study was to determine the preferred regimen regarding toxicity of, response to CRT, and long‐term survival after esophagectomy in EC patients. EC patients in two centers who underwent CRT with different regimens prior to surgery were included in this study. CRT consisted of 50.4Gy combined with two cycles of cisplatin and 5‐FU(center A), or 41.4Gy combined with five cycles of carboplatin and paclitaxel (center B). Toxicity, response to therapy and long‐term survival were compared between groups. One hundred sisty‐five patients were included. Forty‐one percent of patients in center A developed ≥1 toxicity ≥ grade 3 versus 25% in center B (P = 0.025). CRT with a cisplatin‐based regimen was an independent predictor for development of toxicity ≥ grade 3 (P = 0.043). There were no differences in response between both regimens (P = 0.904). Three‐year survival was 61% (A) versus 57% (B) (P = 0.725). The carboplatin/paclitaxel/41.4Gy regimen causes less toxicity compared to the cisplatin/5‐FU/50.4Gy regimen with nonsignificant differences in response rates and long‐term survival; therefore our results support this regimen to be the preferred regimen for EC patients.